Dictionary, Translation and Chinese Language in Domingo Fernández de Navarrete (Sinología hispánica. China Studies Review, 2019)
One of the essential elements of the much-admired accommodation of the Jesuits was their dedication to the study of the Chinese language. However, this orientation is not exclusively to the Jesuits. The other religious orders also showed the same orientation from the first moment. Although following the imperial guidelines of Nebrija evangelization should be done in Spanish, the friars who left for America and Asia were focused from the first moment to learn thelocal languages. Following the line of sixteenthcenturyMexican dictionaries and languages,the translation of texts between Spanish andChinese already had a clear representationin the Philippine Islands with the work of JuanCobo. Throughout the XVII several vocabularies,grammars and language arts would appear whilethe work of the Dominican Domingo Fernández deNavarrete would include a very brief dictionary.This interest of mendicants by the local languageswould culminate in the work of the DominicanFrancisco Varo. Starting from the original sources—manuscripts and printed— of the seventeenthcentury, this communication will analyze in detailthe linguistic accommodation of the mendicantorders with special emphasis on the Franciscansand the Dominicans.